The Tax is right ; Making it work ; Yoyoy Villame yearns [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Examines the new taxes on beer proposed by the Congress. NPA commander and founder, Dante Buscayno leads a farmers' cooperative in Tarlac. Yoyoy Villame talks about his life and his music.
The tax is right (17 min.) -- Making it work (15 min.) -- Yoyoy Villame (13 min.)
VHS.
Keywords: Buscayno, Alex -- Interviews; Villame, Yoyoy -- Interviews; Comprehensive Agrarian Reform Program; Taxation -- Philippines; Taxpayers -- Philippines; Cooperative societies -- Philippines